Bacteriological Quality of Water used for Drinking/Washing-Teeth in Southeastern Nigeria - Dr Peter Okorie; Prof. John Emaimo (International Dental Journal, 2023)
Aim or Purpose: Water is used for its numerous purposes including washing of teeth. Bacteriological deterioration of water has been reported as one of the major cause of waterborne disease globally. The presence of sugar in the mouth has been implicated with dental caries and other notable oral diseases. This study investigates the bacteriological quality of potable water used for drinking and mouth wash among subjects in parts of Southeastern Nigeria. Materials and Methods: The study employed a descriptive cross-sectional design. Oral swab samples collected from volunteers was subjected to bacteriological examination. Potable water samples were also collected for bacteriological studies. Data analysis was done through descriptive and inferential statistics at 5% level of significance (p<0.005) Results: In Abia Central senatorial Zone, the bacteria isolated was Enterococcus faecalis (20.7%) followed by Streptococcus mutans (19%) abundance for oral swabs while Enterococcus faecalis (55.9%) followed by Escherichia coli (20.3%) was recorded for water samples. Abia North senatorial Zone recorded 18.1% Streptococcus mutans and 17.2% Enterococcus faecalis for oral swabs. Enterococcus faecalis (55.9%) and 20.3% Escherichia coli was recorded for water samples. Abia South senatorial Zone recoded 22.2% Enterococcus faecalis and 21.4% Streptococcus mutans in oral swabs while Enterococcus faecalis (55.9%) and Escherichia coli (20.3%) was recorded for water samples. There is a moderate (0.636) association between oral hygiene problems and bacteriological quality of water used in drinking/washing of teeth at p<0.05. Conclusions: This study concludes that microbiologically, the water samples are not of adequate quality. The presence of heterotrophic bacteria and coliforms in all the waters assessed imply that consumers of such waters are vulnerable and at risk of oral infections.